2006
DOI: 10.5194/bg-3-651-2006
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling regional differences in forest soil emission of nitrogen oxides (NO and N<sub>2</sub>O)

Abstract: Abstract. Soil emissions of NO and N 2 O were measured continuously at high frequency for more than one year at 15 European forest sites as part of the EU-funded project NOFRETETE. The locations represent different forest types (coniferous/deciduous) and different nitrogen loads. Geographically they range from Finland in the north to Italy in the south and from Hungary in the east to Scotland in the west.The highest NO emissions were observed from coniferous forests, whereas the lowest NO emissions were observ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
195
7
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 228 publications
(232 citation statements)
references
References 60 publications
28
195
7
2
Order By: Relevance
“…However, more and more attention is being paid to denitrification process in forests under increasing N deposition due to the high global warming potential of N 2 O (Hall and Matson 1999;Levy-Booth et al 2014). Although some studies have shown that N deposition and fertilization to forest ecosystems have minor effects on soil N 2 O emission (Magill et al 1997), there is mounting evidence that excessive N deposition to forest ecosystems, especially to N-unlimited forest ecosystems, has promoted soil N 2 O emission (Butterbach-Bahl et al 1998;Gundersen et al 2012;Hall and Matson 1999;Jassal et al 2011;Pilegaard et al 2006;Zhang et al 2008). For example, Hall and Matson (1999) found that N addition stimulated N 2 O emissions in both phosphorus (P)-limited and N-limited tropical forest soils, with a greater stimulation in the P-limited forest.…”
Section: Denitrification and N 2 O Emissionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, more and more attention is being paid to denitrification process in forests under increasing N deposition due to the high global warming potential of N 2 O (Hall and Matson 1999;Levy-Booth et al 2014). Although some studies have shown that N deposition and fertilization to forest ecosystems have minor effects on soil N 2 O emission (Magill et al 1997), there is mounting evidence that excessive N deposition to forest ecosystems, especially to N-unlimited forest ecosystems, has promoted soil N 2 O emission (Butterbach-Bahl et al 1998;Gundersen et al 2012;Hall and Matson 1999;Jassal et al 2011;Pilegaard et al 2006;Zhang et al 2008). For example, Hall and Matson (1999) found that N addition stimulated N 2 O emissions in both phosphorus (P)-limited and N-limited tropical forest soils, with a greater stimulation in the P-limited forest.…”
Section: Denitrification and N 2 O Emissionmentioning
confidence: 99%
“…Also, estimated N loss as NO could reach up to 24.5-34.5 % of N deposited or added to forests (Butterbach-Bahl et al 2002;Pilegaard et al 2006). Furthermore, it has been reported that the main source for NO in forest soils is nitrification (autotrophic nitrification) (Pilegaard et al 2006;Venterea et al 2003), and the key factors regulating its emission could be soil moisture, soil temperature, litter layer properties (e.g., water content and thickness), N deposition (at least for European coniferous forests), and soil pH (Pilegaard et al 2006;Venterea et al 2003).…”
Section: N Loss and Retention In Forest Soilsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anthropogenic emissions of reactive nitrogen (N) have markedly increased the atmospheric N deposition to forests, especially around industrialized regions (Pinho et al, 2012;Gruber and Galloway, 2008;Galloway et al, 2003). There is, however, a large spatial variability in the effects by N deposition (Magnani et al, 2007;Fischer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%